Reproductive doe traits of the Nubian (Zaraibi) goats in Egypt - Marai, I.F.M.; Abou-Fandoud, E.I.; Daader, A.H.; Abu-Ella, A.A. (Elsevier, 2002)
Nubian does from the hot arid climate of upper Egypt were evaluated for productive and reproductive traits under Nile Delta (lower Egypt) conditions. The mean values for age at first kidding, abortion rate, and mortality rate were 691 days, 1.4 and 26.8%, respectively. Corresponding values for litter size at birth and weaning were 2.9 and 2.3 kids, respectively, and for litter weight at birth and weaning were 4.9 and 25.3 kg, respectively. The lifetime production per doe for kid weight at birth and weaning were 19.8 and 83.7 kg, respectively. Does kidding in November–December surpassed (P